2020
DOI: 10.1155/2020/2421816
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Refractive Outcomes of Cataract Surgeries Performed in One Year in a Private Practice Setting: Review of 2714 Procedures

Abstract: Introduction. Currently available outcome data for cataract surgery include mostly patients from public health systems. The purpose of this study was to report the visual and refractive outcomes of cataract procedures performed during one year in a private practice center, which may include a different spectrum of patients. Methods. Our center’s database was used to identify all isolated cataract procedures performed during 2017. The electronic records were reviewed to collect the preoperative information, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
5
8
1
Order By: Relevance
“…The mean CDVA of all eyes in our study improved from 0.43 ± 0.43 logMAR pre-operatively, to 0.05 ± 0.11 logMAR post-operatively (p < 0.05). Again, this result is comparable to those in recent studies involving similar IOLs [11][12][13][14] . A marginally superior post-operative mean CDVA result has been reported in the EUREQUO 2018 annual report for Cataract and Refractive Surgery 15 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The mean CDVA of all eyes in our study improved from 0.43 ± 0.43 logMAR pre-operatively, to 0.05 ± 0.11 logMAR post-operatively (p < 0.05). Again, this result is comparable to those in recent studies involving similar IOLs [11][12][13][14] . A marginally superior post-operative mean CDVA result has been reported in the EUREQUO 2018 annual report for Cataract and Refractive Surgery 15 .…”
Section: Discussionsupporting
confidence: 90%
“…Again, this result is comparable to those in recent studies involving similar IOLs[11][12][13][14] . A marginally superior post-operative mean CDVA result has been reported in the EUREQUO 2018 annual report for Cataract and Refractive Surgery 15 .However, the smaller percentage of eyes with concomitant ocular pathologies included in this report is a noteworthy factor.…”
supporting
confidence: 90%
“…Previous studies in Africa, Nigeria, and India showed that the average age of patients was 60-65 years old [8]- [10]. Meanwhile, a study in Spain in 2017 had a similar average age of cataract patients with this study, which is 70 years old [11]. Postoperative visual acuity showed gradual improvements.…”
Section: Discussionsupporting
confidence: 69%
“…Advances in technical equipment, surgical procedures, and lens design have improved outcomes. However, reports declared that a postoperative spherical equivalent of ≤ 1.0 diopters can be achieved in 72%-95% of patients, and a spherical equivalent ≤ 0.5 diopters can be achieved in only 45%-80% of the patients (Hamoudi et al, 2013;Rementeria-Capelo et al, 2020). After cataract surgery, a vitrectomy may be required for rhegmatogenous RD, epiretinal membrane, macular hole, or vitreous hemorrhage (Jahn et al, 2001;Patterson et al, 2001;Qureshi and Steel, 2020).…”
Section: Discussionmentioning
confidence: 99%